Peningkatan Kemampuan Membaca Permulaan melalui Media Kartu Kata Bergambar pada Anak Kelompok B di RA Al-Hadda - Lismawati Sitorus; Aminda Tri Handayani; Juli Yanti Harahap; Novita Friska (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
One of the efforts to develop children's potential and abilities is for teachers to possess the skills to provide appropriate stimulation across all developmental domains. One instructional medium that can be used to improve early reading skills is picture word cards. This study aimed to improve the early reading skills of Group B children at RA Al Hadda, Tanjung Morawa District, through the use of picture word cards. The research employed a collaborative Classroom Action Research (CAR) design, conducted jointly by the researcher and the Group B classroom teacher at RA Al Hadda, Tanjung Morawa. Data were collected through observation and documentation. The results indicated that the use of picture word cards effectively improved the early reading skills of Group B children. This improvement was demonstrated by the increase in children's reading achievement across the research cycles. During the pre-action stage, the average achievement score was 42.59%. It increased by 25.75% to 68.34% in Cycle I, and further improved by 27.23% from Cycle I to Cycle II, reaching a final score of 95.57% in Cycle II. These findings demonstrate that picture word cards are an effective instructional medium for enhancing the early reading skills of Group B children at RA Al Hadda, Tanjung Morawa.